Caboclos na Amazônia: a identidade na diferença - RODRIGUES, Carmem Izabel (2012)
This work aims at discussing issues related to essentialness and reification, which are found in identity construction processes, as well as in current worldwide cultural differences claims, particularly the identity (or non-identity) of the Amazonian caboclo. Can we talk about a caboclo identity? If caboclo is not an ethnic category, in the strict sense of the term, then it is in the game of difference that it is constructed, as well as other anthropologic subjects/objects.